Psychiatric morbidity and pattern of dysfunctions in patients with leprosy - Bhatia M; Chandra R; Bhattacharya S; Imran Mohammed (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Leprosy, being a chronic infectious disease with profound social stigma, remains associated with high psychological mortidity. PURPOSES: To find out the pattern of psychiatric morbidity in leprosy patients and the relationship of various factors with the morbidity. METHODS: Ninty patients attending leprosy clinic were randomly chosen for the study group alongwith 40 patients suffering from acute skin problem other than leprosy as control group. The socio-demographic data were recorded in semi-structural proforma; all patients were given Goldbery Health Questioneaire (GHQ). Patients having GHQ score> 2 was assessed by Disability Assessent Questionaire (DAQ). The psychiatric diagnoses was made according to ICD-10 by W ho0 and physical deformity by W ho 0 Disability Scale. FINDINGS: The mean GHQ score of the study grant was 3.44 and that of control group was 1.62. The mean DAQ score was 45.13. Psychiatric disorder was seen in 44.4% and 7.5% of study group and control group respectively. The psychiatric illness was generalised anoxidy disorder (GAD) (27.8%). CONCLUSIONS: Leprosis highly associated with psychiatric mobidity. LIMITATIONS: The findings can not be generalised due to small sample size and clinic-based data.